Internal Validation of A Six Non-Codis Ministr Loci (D1s1627, D3s4529, D5s2500, D6s1017, D8s1115 And D9s2157) System - Abrahams-October, Zainonesa; Pearce, Brendon; Benjeddou, Mongi (The International Journal of Biotechnology, 2014)
Non-CODIS (NC) miniSTR genotyping systems were developed to produce smaller amplicons by moving the primers as close as possible to the repeat region of interest. These systems are valuable when profiling degraded or compromised DNA samples. This study details the internal validation for a six NC miniSTR system comprised of the loci: D1S1627, D3S4529, D5S2500, D6S1017, D8S1115 and D9S2157. These loci demonstrated the ability to produce consistent, accurate and precise genotype profiles for low concentrations of template DNA. Template DNA concentrations as low as 50pg were successfully amplified and typed. Differentiation of major and minor components were easily identifiable in miniplex 1, but in miniplex 2 complete profiles for each contributor was only observed from ratios ≤1:4. This internal validation allowed for the determination of the reliability as well as the limitations of this NC miniSTR genotyping system.